THE ROLE OF THE SERVICE SECTOR IN THE DEVELOPMENT OF THE COUNTRY - Urunbaeva Yulduz Pirnazarovna (American Journals, 2023)
The content and essence of the service sector in the article and the socio-economic significance of its rapid development, employment of the population in the service sectors an analysis of their structural structures is presented. A comparative analysis of certain data with the regions of Uzbekistan and Samarkand was made.
Keywords: national economy, post-industrial society, economic system, material production, service, paid services, unpaid services, competition, Digital Economy, Innovation, modernization, population standard of living, quality of life, pandemic, demand, consumption, Population Fund,salary, population income.